Supply Chain Agility in The Influence of Strategic Leadership - Amrullah, Ezar; Yuniar, Miandhani Denniz (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2025)
Supply chains must be able to adjust quickly in a dynamic and uncertain global business environment. The VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era demands that organisations and their alliances be proactive in anticipating and responding to change, rather than merely reacting to it. Supply chain agility is a crucial component that enables businesses to adapt, innovate, and maintain their competitive edge in rapidly changing market conditions. Building supply chain agility is therefore essential for maintaining business continuity and ensuring customer satisfaction. Previous literature from 2019 to 2025 was analyzed using a content analysis approach that aims to discuss the role of strategic leadership in building Supply Chain Agility (SCA). In this context, the role of innovation and digital transformation is shifting the paradigm from proactive to transformative. Dynamic capabilities serve as amplifiers, magnifying the positive effects of strategic leadership on supply chain agility. Resource orchestration bridges the gap between leadership decisions and the supply chain's achieved level of agility. This study affirms organisations need to consider building agility in conjunction with technological investment and process restructuring. However, organisations must prioritise the quality of strategic leadership that is capable of navigating uncertainty. Strategic leaders drive innovation, resilience, and cross-boundary collaboration within supply chains.Keywords - Digital Transformation, Resource Orchestration, Strategic Leadership, Supply Chain Agility, VUCA.